2010
DOI: 10.1590/s0103-64402010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodontal therapies on indirect restoration: a scanning electron microscopic analysis

Abstract: The aim of this study was to evaluate the influence of different periodontal therapies on the integrity of indirect restorations by scanning electron microscopy (SEM). Sixty single-rooted bovine teeth were selected and randomly assigned to 12 groups. Inlay cavities were prepared in the cervical region on the center of the cementoenamel junction, and were restored with laboratory processed resin and luted with a resin cement. Twelve periodontal therapies were used (n= 5): C: control (no treatment); MS: manual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(43 reference statements)
0
6
1
1
Order By: Relevance
“…Nonetheless, in the present study, both APD and pumice-and-rubber-cup techniques resulted in more gap formation compared to the control group. One of the reasons for the difference between the results of the latter study, 5 and those of ours might be the nature of the evaluated materials and their surface characteristics. The resistance of tooth-colored restorative materials to abrasion might be influenced by the type of the resin, the size and percentage of the fillers, and the polymerization technique used.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Nonetheless, in the present study, both APD and pumice-and-rubber-cup techniques resulted in more gap formation compared to the control group. One of the reasons for the difference between the results of the latter study, 5 and those of ours might be the nature of the evaluated materials and their surface characteristics. The resistance of tooth-colored restorative materials to abrasion might be influenced by the type of the resin, the size and percentage of the fillers, and the polymerization technique used.…”
Section: Discussioncontrasting
confidence: 76%
“… 17 Salami et al 18 reported that use of APD resulted in abrasion of root surfaces and destruction of restorations and resin cements. Soares et al 5 using electron microscope evaluations reported that APD destroyed the cement line in indirect composite resin restorations and produced a rough and porous surface. In addition, it formed gaps at the restoration‒tooth interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional scaling and root planning are essential procedures in periodontal therapy (10) and rely on mechanical removal of plaque, calculus, root-bound toxins and contaminated cementum (11). A viable dental plaque covers calculus deposits, which contributes substantially to the pathogenesis of bacteria-induced periodontal disease (12). The main goal of periodontal therapy is to reduce inflammation and allow new epithelial attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Penentuan penilaiaan status periodontal dapat ditentukan dengan hasil radiografi (Kortegaard et al 2014). Tindakan yang dilakukan untuk mengurangi mikroba dalam menangani penyakit periodontal antara lain scaling, root planning (Fernandes et al 2010), dan mengontrol infeksi yang terjadi di area gingiva (Soares et al 2010). …”
Section: ■ Pendahuluanunclassified